2017
DOI: 10.1161/jaha.117.007673
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methyltransferase 1–Dependent DNA Hypermethylation Constrains Arteriogenesis by Augmenting Shear Stress Set Point

Abstract: BackgroundArteriogenesis is initiated by increased shear stress and is thought to continue until shear stress is returned to its original “set point.” However, the molecular mechanism(s) through which shear stress set point is established by endothelial cells (ECs) are largely unstudied. Here, we tested the hypothesis that DNA methyltransferase 1 (DNMT1)–dependent EC DNA methylation affects arteriogenic capacity via adjustments to shear stress set point.Methods and ResultsIn femoral artery ligation–operated C5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 85 publications
(161 reference statements)
2
20
0
Order By: Relevance
“…Interestingly, and consistent with the previously described study, increased expression of DNMT1 observed under unidirectional flow resulted in reduced monocyte adhesion to ECs which was reversed by treatment with 5azadC in both in vitro and in vivo models [72]. Notably, when ECs maintained under shear stress were exposed to reversed flow, DNMT1 expression remained unaltered whilst monocyte adhesion to ECs was increased, prompting the authors to propose that hypermethylation under shear stress with unilateral flow may limit the arteriogenic capacity of ECs, thereby preventing hypertrophy/hyperplasia which may lead to impaired perfusion and tissue hypoxia [72]. In addition to DNMT1, other DNMT enzymes have been implicated in regulating EC function in response to altered blood flow.…”
Section: Ischaemia-induced Endothelial Cell Dysfunctionsupporting
confidence: 91%
See 2 more Smart Citations
“…Interestingly, and consistent with the previously described study, increased expression of DNMT1 observed under unidirectional flow resulted in reduced monocyte adhesion to ECs which was reversed by treatment with 5azadC in both in vitro and in vivo models [72]. Notably, when ECs maintained under shear stress were exposed to reversed flow, DNMT1 expression remained unaltered whilst monocyte adhesion to ECs was increased, prompting the authors to propose that hypermethylation under shear stress with unilateral flow may limit the arteriogenic capacity of ECs, thereby preventing hypertrophy/hyperplasia which may lead to impaired perfusion and tissue hypoxia [72]. In addition to DNMT1, other DNMT enzymes have been implicated in regulating EC function in response to altered blood flow.…”
Section: Ischaemia-induced Endothelial Cell Dysfunctionsupporting
confidence: 91%
“…Similarly, elevated DNMT1 levels in response to perturbed blood flow were attenuated with 5aza treatment [71]. Other studies have also reported increased DNMT1mediated DNA methylation in the context of both increased shear stress (induced in vivo by vascular occlusion or in vitro using cone and plate flow apparatus) and unidirectional flow, associated with global hypermethylation of genes associated with cellular metabolism, nucleic acid turnover and transcription [72]. Interestingly, and consistent with the previously described study, increased expression of DNMT1 observed under unidirectional flow resulted in reduced monocyte adhesion to ECs which was reversed by treatment with 5azadC in both in vitro and in vivo models [72].…”
Section: Ischaemia-induced Endothelial Cell Dysfunctionmentioning
confidence: 81%
See 1 more Smart Citation
“…Further supporting this hypothesis, the ERASE trial found that a combination therapy of revascularization and exercise improved functional outcomes of PAD patients compared to just exercise alone (Fakhry et al, 2015 ). Overexpression of miR-93 (Ganta et al, 2017 ) or miR-199a inhibition (Heuslein et al, 2017 ) have both been shown to be capable of inducing arteriogenesis and improving in the ischemic downstream tissue, demonstrating such miR-based approaches are indeed possible.…”
Section: Discussionmentioning
confidence: 99%
“…We used a previously detailed FAL scheme (Meisner et al, 2012 ; Heuslein et al, 2015b , 2016 , 2017 ) that produces consistent arteriogenesis in the collateral arteries of the gracilis adductor muscles (Chappell et al, 2008 ; Distasi et al, 2009 ; Nickerson et al, 2009a ; Dai and Faber, 2010 ; Meisner et al, 2013 , 2014 ; Heuslein et al, 2015b , 2016 , 2017 ), along with minimal heterogeneity in the baseline collateral structure with known changes in flow direction from baseline. Male mice, 10–12 weeks of age, were anesthetized (i.p.…”
Section: Methodsmentioning
confidence: 99%